Use of Phytotherapics, Low Power Laser and Ozone for Biting Wound in Dog - de Cantuário Ferreira, Paulo Geovane; Inocêncio Cunha, Leonardo; Gomes Rabelo, Pâmella; Tâmara da Silva Rocha, Any; Giarola Boscarato, André; Alberton, Luiz Romulo; Faria Orlandini de Andrade, Carla (Acta Scientiae Veterinariae, 2020)
Background: Skin wounds are among the most common cases in small animals, highlighting the importance of alternative therapies as an aid to the healing process. These include ozone, which has a bactericidal and immunomodulatory action; the low power laser that determines photodynamic changes triggering metabolism elevation; and the use of medicinal plants, in which several herbal medicines has been mentioned in research relating their benefits to wound healing in humans and animals. Thus, it aims to report the case of a dog submitted to these treatments due to chronic wound due to bite. Case: A 6-year-old canine, female, mixed-breed, 8 kg, with a perforating wound in the left anterior limb in the scapular and humeral region, caused by trauma from the bite of another dog, previously treated, without clinical improvement, has been attended presenting apathy, increased body temperature (40.1°C), difficulty in walking and inability to support the injured limb, which was swollen, hyperemic, with elevated temperature, absence of hair, elevated pain sensitivity and presence of 2 circular lesions, approximately 2 cm in diameter, caused by trauma, and others of size between 0.5 and 1 cm in diameter, which appeared during the course of the disease, characterized as fistulas, through which there was drainage of characteristic fluid exudative and purulent discharge. It was collected blood sample for blood count and purulent material through sterile swab for culture and antibiogram. Systemic treatment with ceftiofur, dipyrone, meloxican and topical cleaning of the wounds with hydrogen peroxide and physiological solution; dimethyl sulfoxide ointment, and hot compresses was chosen. After seven days, the animal showed significant general clinical improvement and in the limb, it was observed: decreased edema, hyperemia, hyperthermia and secretions, with no pus. Only local treatment was recommended, with cleansing of the skin lesions, with physiological solution, chlorhexidine and healing gel made of herbal medicine: chitosan, aloe vera, marigold, sunflower oil and barbatimao. After 21 days of treatment, the injured limb showed consecutive clinical improvement, with epithelialization of the smaller diameter lesions. Low-level laser and ozone therapy was instituted, totaling three initial sessions every five days and one last session 14 days after the third. After the four sessions the animal was discharged, presenting absence of the previously reported alterations, besides the total re-epithelialization of the lesions and hair growth. Discussion: The contamination arising from bite can interfere with healing time due to the action of bacterial toxins and inflammatory infiltrates that cause vascular and cellular damage. According to other reports the use of ozone therapy, local and systemic, promoted rapid healing, related to effective decontamination, in a short period of time. Considering the response and quality of tissue repair, due to wound recovery, verifying therapeutic effects of anti-inflammatory action, effective decontamination, stimulation of granulation tissue, epithelialization and repilation of the cutaneous region, it is concluded that topical and systemic ozone therapy, associated with the effect of tissue regeneration by edge revival in chronic lesions, of low power laser and herbal medicine gel, under the conditions of this case, represent satisfactory therapy for the treatment of bite wounds in dogs.